Intersectional Feminism in Islam: An Analysis of Leila Ahmed’s Thoughts on Colonialism, Gender, and Religion - Abdul Kamal Sungkar; Sohibul Aslam; Latifah Islami; Nur Armaini Fadilah; Annisa Munawwarah (Arba: Jurnal Studi Keislaman, 2026)
The dominance of Western feminist discourse often positions Muslim women as symbols of cultural and religious backwardness, a construct reinforced by colonial narratives and still influencing contemporary representations of Muslim women. Although various studies have examined Islamic feminism, intersectional analyses of Leila Ahmed’s thought, which integrally links colonialism, gender, and religion, are still limited. This study aims to specifically examine how Ahmed dismantles the instrumentalization of women’s issues by colonial powers, distinguishes normative Islamic teachings from patriarchal practices, and formulates her contribution to the development of contemporary Islamic feminism. The method employed is a qualitative approach, utilizing a critical discourse analysis model by Norman Fairclough, which encompasses three main dimensions: text analysis, discourse practice, and social practice. The results of the study show three main findings: first, Ahmed uncovers colonial strategies that instrumentalize women’s issues to strengthen political and cultural domination; second, Ahmed asserts that the oppression of Muslim women stems more from patriarchal social constructions than from Islamic teachings themselves; third, Ahmed offers a reinterpretation of tradition as a dynamic arena for women to build spiritual and intellectual authority. In conclusion, Ahmed’s thinking presents a critical framework that enriches contemporary Islamic feminism by emphasizing the importance of an intersectional approach in reading the power relations between colonialism, gender, and religion, while also opening up space for further research on women’s interpretive practices in postcolonial contexts.